2014
DOI: 10.1007/s40618-014-0156-8
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 receptor agonist increases the expression of CTRP3, a novel adipokine, in 3T3-L1 adipocytes through PKA signal pathway

Abstract: GLP-1 receptor agonist increases the expression of CTRP3 mRNA and protein in 3T3-L1 adipocytes via PKA signal pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…CTRP3 can function in an autocrine, paracrine, and endocrinemanner and there are many aspects of CTRP3’s regulation and function that have yet to be explored. In addition, CTRP3 has been consistently linked to activation of the PKA signaling pathway, regardless of the tissue/treatment paradigm examined (37, 47, 80). This review should serve as a basis for the design of future experimental studies specifically examining: (i) the regulation of CTRP3 in response to food intake or exercise, (ii) associations between circulating CTRP3 levels, including the two different splice variants (CTRP3A and CTRP3B), and hepatic steatosis or osteoscarcoma in clinical population, and (iii) the associations between the different CTRP3 isoforms (CTRP3A and CTRP3B) and multimeric structures in clinical populations, (iv) the potential use of CTRP3 as an inhibitor of inflammation, and (v) whether the putative receptors, LAMP1 and LIMPII are directly responsible for the intracellular effects of CTRP3 or at as coreceptors for a yet unidentified protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CTRP3 can function in an autocrine, paracrine, and endocrinemanner and there are many aspects of CTRP3’s regulation and function that have yet to be explored. In addition, CTRP3 has been consistently linked to activation of the PKA signaling pathway, regardless of the tissue/treatment paradigm examined (37, 47, 80). This review should serve as a basis for the design of future experimental studies specifically examining: (i) the regulation of CTRP3 in response to food intake or exercise, (ii) associations between circulating CTRP3 levels, including the two different splice variants (CTRP3A and CTRP3B), and hepatic steatosis or osteoscarcoma in clinical population, and (iii) the associations between the different CTRP3 isoforms (CTRP3A and CTRP3B) and multimeric structures in clinical populations, (iv) the potential use of CTRP3 as an inhibitor of inflammation, and (v) whether the putative receptors, LAMP1 and LIMPII are directly responsible for the intracellular effects of CTRP3 or at as coreceptors for a yet unidentified protein.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin immunoprecipitation assay confirmed that c-Jun binds to the AP-1 region (-184/-177) of CTRP3 (28), whereas, other Jun and Fos members JunB, JunD, FosB, Fra-1, and Fra-2 were tested by a reporter gene assay and had no effect on CTRP3 promoter activity (28). Further, treatment of adipocytes, in vitro , or diet-induced obese rats, in vivo , with the glucagon-likepeptide-1 (GLP-1) receptor agonist, Exendin-4 (Ex-4), increased CTRP3 expression and circulating levels through activation of the Protein kinase A (PKA) pathway (37,40). Briefly, the activation ofGLP-1 receptor and PKA pathway activates HOB1 motif within the A1 activation domain of c-JUN and promotes c-JUN’s binding to the AP-1 region (6).…”
Section: History Of Ctrp3mentioning
confidence: 99%
“…Those with a history and evidence of myocardial infraction, stroke, kidney disease, cancer, autoimmune diseases, chronic inflammation and treated with thiazolidinedione family drugs were excluded from study. Using thiazolidinedione was an exclusion criteria because the CTRP3 promoter have a peroxisome proliferator-activated receptor (PPAR) response element and also upregulate expression of CTRP13 and other CTRP family member [17,20], Subjects received no glucagon-like peptide-1 receptor agonists which upregulate CTRP3 expression [21]. Arterial hypertension was defined as SBP≥140mm Hg, DBP≥90mm Hg in repeat measurement or current use of antihypertensive medication.…”
Section: Methodsmentioning
confidence: 99%
“…However, higher CTRP-3 levels were found in patients suffering from type 2 diabetes mellitus [17]. As glucagon-like peptide-1 (GLP-1) receptor agonists increase the expression of CTRP-3 in adipocytes [21,22] in vitro, a possible effect of orally administered glucose or lipids on serum CTRP-3 levels would be of interest. A cross-sectional study by Wolf et al [20] reported lower CTRP-3 concentrations in obese individuals.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional study by Wolf et al [20] reported lower CTRP-3 concentrations in obese individuals. As glucagon-like peptide-1 (GLP-1) receptor agonists increase the expression of CTRP-3 in adipocytes [21,22] in vitro, a possible effect of orally administered glucose or lipids on serum CTRP-3 levels would be of interest. Data on the physiological and postprandial regulation of serum CTRP-3 in healthy individuals are not available, and it is not known whether CTRP-3 is able to penetrate the blood-brain barrier and can be measured in cerebrospinal fluid (CSF).…”
Section: Introductionmentioning
confidence: 99%